Prevalence of sexual dysfunctions in the puerperium of cesarean delivery (Research, Society and Development, 2021)
Objective: To describe the prevalence of sexual dysfunctions in the postpartum period of Cesarean delivery. Methodology: Descriptive observational study, the sample size was 30 postpartum women. Being developed digitally, through a form created in Google Forms from October 2020 to April 2021. The first step included filling in the sociodemographic data on the form and then applying the Female Sexual Function Index (FSFI), a self-report with 19 items covering six sexual domains (desire, arousal, lubrication, orgasm, satisfaction and pain), in the last four weeks, the patient selects one of the answers that best represents her, the alternative 0 indicates that she did not have sexual intercourse and the others range from 1 to 5. The final sum gathers the responses from all domains. Statistical analysis was descriptive. Results: Among the volunteers, 80% of the population is aged between 19-29 years old and 43.3% of the women are married, 53.3% of the women have completed higher education. 70% of the sample was pregnant only once and 76.6% had only 1 cesarean at the time of research. Regarding desire, 36.7% of women reported feeling sexual desire or interest a few times. When asked about sexual satisfaction, 53.3% reported being very satisfied with the intensity of emotional intimacy with their partner. Conclusion: This study showed that women participating in the research who were in the postpartum period of Cesarean delivery did not present a DSF, but a moderate change in sexual activity.